Kontribusi Muhammadiyah Dalam Penguatan Demokrasi Dan Stabilitas Pemerintahan Di Indonesia - Sugeng Aji Prasetyo; Zayyati Etwina (Penerbit Minhaj Pustaka, 2024)
This study aims to discuss Muhammadiyah's contribution to strengthening democracy and government stability in Indonesia. As the largest Islamic organization in Indonesia, Muhammadiyah plays a role through political education, strengthening civil society, and advocating policies that support good governance. In addition, Muhammadiyah mediates social conflicts and maintains the value of moderation, which contributes to social harmony. With the principles of moderation and neutrality, Muhammadiyah has succeeded in maintaining a balance between constructive criticism of the government and collaboration in national development. This study emphasizes the importance of Muhammadiyah's role as a major actor in realizing inclusive democracy and government stability in Indonesia. Abstrak Penelitian ini bertujuan untuk membahas kontribusi Muhammadiyah dalam penguatan demokrasi dan stabilitas pemerintahan di Indonesia. Sebagai organisasi Islam terbesar di Indonesia, Muhammadiyah berperan melalui pendidikan politik, penguatan masyarakat sipil, dan advokasi kebijakan yang mendukung tata kelola pemerintahan yang baik. Selain itu, Muhammadiyah menjadi mediator konflik sosial dan penjaga nilai moderasi, yang berkontribusi pada harmoni masyarakat. Dengan prinsip moderasi dan netralitas, Muhammadiyah berhasil menjaga keseimbangan antara kritik konstruktif terhadap pemerintah dan kolaborasi dalam pembangunan nasional. Studi ini menegaskan pentingnya peran Muhammadiyah sebagai aktor utama dalam mewujudkan demokrasi yang inklusif dan stabilitas pemerintahan di Indonesia.